Inclusive Growth toward a Harmonious Society in the People's Republic of China: An Overview - Lin, Justin Yifu (2012)
This overview introduces the background of the study "Inclusive Growth toward a Harmonious Society in the People's Republic of China (PRC)", under which all the papers in this special volume were prepared. It summarizes key findings of these papers as grouped into three parts: (i) Inclusive Growth and Policy Options; (ii) Balancing Efficiency and Equity Objectives: International Experiences; and (iii) Empirical Analysis of Income Inequalities in the PRC. In concluding, this overview argues that building a harmonious society is the most important development challenge that the PRC faces, and that a development strategy anchored on inclusive growth provides an effective approach to addressing this issue.